Emotional Responses to Reading in the First Grade - The “L.E.R. Cãofiante” Project - Mata,Lourdes (2020)
Abstract The “L.E.R. Cãofiante”* project was implemented with first-grade pupils who took part in reading sessions animated by a librarian in partnership with her dogs. The goal was to evaluate the effect of this intervention on children’s emotions regarding reading (enjoyment, anxiety, boredom). The participants were 80 children (47 in the Intervention Group (IG); 33 in the Comparison Group (CG)). Parents and teachers answered a questionnaire about children’s involvement, and the children answered one about reading emotions. For data processing, repeated measures ANOVA was used along with content analysis of the answers to the questionnaires. The results showed different emotional profiles of children in the IG and the CG, mostly regarding enjoyment, which increased in the IG. Data from parents and teachers corroborated this conclusion, emphasising positive experiences which allowed an understanding of the role of dogs in children’s enjoyment and interest in reading.